Design TPACK Strategy with Modellus Software for Simulation Based on The Guided Inquiry on The Wave Concept - Muniyatun Hasanah; Dwi Sulisworo (Jurnal Ilmiah Pendidikan Fisika, 2022)
Technological Pedagogical and Content Knowledge (TPACK) is a teacher framework in integrating Information and Communication Technology (ICT) in learning. The purpose of the initial learning planning by implementing the guided inquiry-based TPACK strategy is to increase the mastery of concepts and student learning activities. This research uses the literature review method with qualitative predictive analysis. Object research is an information system with the reason that there is a change in the application of information systems that were once still conventional, now began to be computerized and the development of information systems can be on various platforms, Among others, the web, desktop, mobile, and the last reason being that the development of information system systems has a variety of methods. Initial planning of learning using TPACK-based guided inquiry effectively improves students' mastery of concepts. The subjects were transversal and longitudinal waves with Modellus software. In general, this initial design is that learning with guided inquiry-based TPACK strategies increases mastery of concepts and student learning activities.